Fish, Gymnotiformes, Apteronotidae, Apteronotus magdalenensis (Miles, 1945): Distribution extension of an endangered endemic knifefish, in northern Colombia (2009)
ABSTRACT: The family Apteronotidae Jordan 1823 has recently been reviewed and currently has 60 species recognized as valid (Albert and Crampton 2009). This family has a widespread distribution in South America from Panama to Argentina (Albert 2003) and is the most diverse family of knifefishes in the Amazon basin (Albert 2001; Albert and Campos-da-Paz 1998). MaldonadoOcampo et al. (2008) documented thirty species of Apteronotidae from Colombia, eight endemic species from trans-Andean drainages and four species restricted to the Magdalena river basin (A. eschmeyeri de Santana et al 2004, A. magdalenensis, A. mariae (Eigenmann & Fisher 1914), and A. milesi de Santana & Maldonado-Ocampo 2005).